Ebierbing (ca. 1837-ca. 1881) - Loomis, Chauncey (ARCTIC, 1986)
Ebierbing, called "Joe" by the many whaling men and explorers who knew him, was a small and diffident man, but in the course of a hard life he consistently displayed remarkable strength, courage, and fortitude, as well as unswerving loyalty to those non-Inuit "kabloonas" who came to depend upon him. Foremost among those who benefited from Ebierbing's loyalty was the American explorer Charles Francis Hall. Hall first met Ebierbing and his wife Tookoolito, known as "Hannah," at the mouth of Frobisher Bay in the autumn of 1860. Some years earlier, Ebierbing and Tookoolito had been taken to England by a whaling captain. There they had learned some English and had converted to Christianity; . For Hall, a neophyte explorer on his first venture into the Arctic, they were God sent. In the two years that followed they introduced him to the ways of the Inuit and taught him how to survive in the far North. When they were not on the road with the remorselessly energetic Hall, they were able to find peace and quiet at the home of whaling captain Sidney Buddington and his wife at Groton, Connecticut. They came to consider Groton their home, in fact, and when they returned with Hall from his second expedition, Ebierbing bought a house and land there. Hall's second expedition, like his first, was a futile search for supposed survivors of the Franklin expedition almost twenty years after it had disappeared. In five arduous years of roaming in the areas of Roe's Welcome Sound, Repulse Bay, Igloolik, and King William Island, he accomplished little but his own survival, and in that accomplishment Ebierbing and Tookoolito again were his mainstay. . The Polaris expedition was a disaster. Hall died early on, possibly murdered by its chief scientist, and with his death the morale of the expedition collapsed. In the spring of 1873 the ship's captain, Sidney Buddington, headed the Polaris southward. Caught in ice during a storm, he ordered abandonment of the ship. Nineteen members of the expedition, including Ebierbing, Tookoolito, and ...